2011
DOI: 10.1007/s10661-011-2059-x
|View full text |Cite
|
Sign up to set email alerts
|

Water quality and dissolved inorganic fluxes of N, P, SO4, and K of a small catchment river in the Southwestern Coast of India

Abstract: The southwestern coast of India is drained by many small rivers with lengths less than 250 km and catchment areas less than 6,500 km(2). These rivers are perennial and are also the major drinking water sources in the region. But, the fast pace of urbanization, industrialization, fertilizer intensive agricultural activities and rise in pilgrim tourism in the past four to five decades have imposed marked changes in water quality and solute fluxes of many of these rivers. The problems have aggravated further due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 23 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…The obtained research results indicate that the land use shapes the structure of waterside water quality, as well as affects the condition of watercourses, especially in terms of their content of nitrates, phosphates and sulfates (Akan et al 2012 ; Wallender and Tanji 2012 ) and sodium, potassium, calcium, sodium and magnesium cations (Purandara et al 2012 ). The most Ca, Mg, Na, K, Fe, N-NO 2 , Cl − and SO 4 were found in waters flowing through a field complex in the spring (Padmalal et al 2012 ). According to Bu et al ( 2017 ), this process is associated with greater biological sorption of minerals by plants grown in summer, and smaller by plants in the spring.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained research results indicate that the land use shapes the structure of waterside water quality, as well as affects the condition of watercourses, especially in terms of their content of nitrates, phosphates and sulfates (Akan et al 2012 ; Wallender and Tanji 2012 ) and sodium, potassium, calcium, sodium and magnesium cations (Purandara et al 2012 ). The most Ca, Mg, Na, K, Fe, N-NO 2 , Cl − and SO 4 were found in waters flowing through a field complex in the spring (Padmalal et al 2012 ). According to Bu et al ( 2017 ), this process is associated with greater biological sorption of minerals by plants grown in summer, and smaller by plants in the spring.…”
Section: Discussionmentioning
confidence: 99%
“…Over-dependence on the groundwater resources and human interventions in the catchments has often led to large-scale decline in the quantity and quality of the groundwater resources even in mountainous catchments (Guo and Wang, 2005;Peisert and Sternfeld, 2005;Vaux, 2007;Sadoff and Muller, 2009;Padmalal et al,2011;Vaux, 2011;Hallouche et al, 2017;Kaushal et al,2017). Social and economic activities of the catchments are mostly dependent on the availability and quality of groundwater for various purposes (Hosseinifard and Aminiyan, 2015;Elgallal et al, 2016;Chandran et al, 2017;Wu et al, 2017;Jampani et al, 2018 andPincetti-Zúniga et al,2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, these criteria included only physicochemical parameters (Murray et al, 2001). Indeed, several studies have shown that urbanisation increases the concentration of some nutrients, such as nitrogen, ammonia, nitrate, and phosphorus, decrease the concentration of oxygen and is responsible for pH changes in rivers and streams (Hoare, 1984;Meybeck, 1998;Wernick et al, 1998;Martinelli et al, 2010;Cumar and Nagaraja, 2011;Padmalal et al, 2012). However, the analysis of the chemical and physical characteristics of an ecosystem becomes limited when the objective is the understanding of its complexity as the biological components should also be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been shown that urbanisation is related to the incresase in nitrogen, ammonium and nitrate levels (Hoare, 1984;Meybeck, 1998;Wernick et al, 1998;Martinelli et al, 2010;Cumar and Nagaraja, 2011;Padmalal et al, 2012), one can hypothesise that it could influence the density and diversity of nitrifying and denitrifying microbes in impacted ecosystems. Considering the global nitrogen cycle, nitrification and denitrification are important steps.…”
Section: Introductionmentioning
confidence: 99%